1930
DOI: 10.2307/209131
|View full text |Cite
|
Sign up to set email alerts
|

Surveys in Hispanic America: Notes on a New Map Showing the Extent and Character of Surveys in Hispanic America

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Geographical Society is collaborating with JSTOR to digitize, preserve and extend access to Geographical Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…1). 31 This map showed that reliable information was strongly associated with the major rivers, national borders and areas of agricultural settlement. In the white 'unsurveyed' areas, AGS compilers were limited to existing published maps and atlases, the most important of which were described as 'mother maps'.…”
Section: The Production Process: Sources and Designmentioning
confidence: 95%
“…1). 31 This map showed that reliable information was strongly associated with the major rivers, national borders and areas of agricultural settlement. In the white 'unsurveyed' areas, AGS compilers were limited to existing published maps and atlases, the most important of which were described as 'mother maps'.…”
Section: The Production Process: Sources and Designmentioning
confidence: 95%
“…Maps based on surveys were further subdivided according to the type of survey: triangulation with precise topographic survey; reliable traverses; triangulation of approximate topography from plane-table sketches or traverses; approximate traverses and compass sketches. As custodian to the largest collection of contemporary Latin American maps in the world by the mid-1920s, the AGS was well placed to publish the first overview of the quality of surveying and mapping for the whole of Latin America and to review the wider literature on the continent's geography (Platt 1930 and1943).…”
Section: The Making Of the Hispanic Mapmentioning
confidence: 99%